The potential of activator protein 1 (AP-1) in cancer targeted therapy - Song, Dandan; Lian, Yan; Zhang, Lin (Frontiers in Immunology, 2023)
Activator protein-1 (AP-1) is a transcription factor that consists of a diverse group of members including Jun, Fos, Maf, and ATF. AP-1 involves a number of processes such as proliferation, migration, and invasion in cells. Dysfunctional AP-1 activity is associated with cancer initiation, development, invasion, migration and drug resistance. Therefore, AP-1 is a potential target for cancer targeted therapy. Currently, some small molecule inhibitors targeting AP-1 have been developed and tested, showing some anticancer effects. However, AP-1 is complex and diverse in its structure and function, and different dimers may play different roles in different type of cancers. Therefore, more research is needed to reveal the specific mechanisms of AP-1 in cancer, and how to select appropriate inhibitors and treatment strategies. Ultimately, this review summarizes the potential of combination therapy for cancer.